Zero-deforestation commitments in Indonesia’s palm oil sector achieve high compliance but no additionality - Matthieu Stigler; Janina Grabs; Robert Heilmayr; Kimberly M. Carlson; Adelina Chandra; Jason Jon Benedict; Rachael D. Garrett (Proceedings of the National Academy of Sciences, 2026)
In response to public pressure, companies have increasingly adopted voluntary sustainable sourcing commitments. Yet, it often remains unclear whether such commitments lead only to the narrow goal of supplier compliance, or also to the broader goal of additionality, benefits beyond what would have occurred without commitments. A company’s ability to influence its suppliers’ behavior partly depends on the complexity of supply chains, yet data on supply chain linkages are limited, inhibiting causal evaluations. Here, we evaluate the compliance and additionality of zero-deforestation commitments (ZDCs) in the Indonesian palm oil sector, a major driver of tropical deforestation. We compiled a detailed dataset that integrates information about corporate ZDC implementation, supply chain linkages, and maps of palm-driven deforestation in Indonesia. We use this dataset to evaluate the causal impact of ZDCs on deforestation in oil palm concessions from 2018 to 2020 using difference-in-differences econometric methods. We find that concessions linked to companies with ZDCs had low deforestation (<1% per year from 2018 to 2020) and thus largely achieved compliance. Yet they experienced similar reductions in deforestation compared to concessions not covered by ZDCs, therefore showing no additionality. We attribute our finding of no additionality to broader changes in policy and economic conditions during the study period that may have reduced the remaining accessible forest and dampened market and regulatory incentives to clear forests for palm oil. Should these conditions change in the future, continued compliance with ZDCs could yield additional reductions in deforestation.